Proinflammatory role of monocytes in SARS-CoV-2 infection in chronic hemodialysis patients - Bumbea, Viorica; Ardelean, Luminita; Radulescu, Luminita; Damian, Luminita; Bumbea, Horia; Dumitru, Ion; Lambert, Claude; Vladareanu, Ana-Maria (Frontiers in Immunology, 2023)
Background Fully mature monocytes that express CD14, but not CD16, undergo phagocytosis within tissues, whereas non-classical monocytes, CD14-low CD16+, represent <11% of peripheral monocytes and have primary pro-inflammatory functions. Inflammation plays a major role in Covid-19 disease and adds to the inflammation caused by chronic hemodialysis. The aim of our study was to monitor monocyte subsets in five patients with end-stage kidney disease (ESKD) over a 1-year period after a mild Covid-19 infection. Five ESKD patients with a mild Covid-19 infection were monitored using CD14, CD16, CD300e, HLA-DR, CD64, and CD45 panels using a BD FACS Canto flow cytometer. Results CD14-low CD16+ was dramatically (p=0,001) decreased in patients during Covid-19 infection, as previously described for patients without chronic renal failure. In addition, CD14-low CD16+ monocytes remained decreased for 10 months after recovery from Covid. Intermediate monocytes increased during Covid-19 infection and decreased 10 months after infection but this subtype of monocytes retained their inflammatory activity with a significant increase in HLA-DR expression after recovery from Covid infection. Conclusion Our study shows that ESKD patients had a pro-inflammatory profile induced by Covid 19, but this status was prolonged significantly over a 10-month period. Thus, advanced renal failure treated by hemodialysis did not dramatically change the inflammatory response against to SARS Covid 2. It seems that monocytes retain their inflammatory status for many months in ESKD patients after a Covid-19 infection.